THE DEVELOPMENT OF A HYPERCONTENT-BASED LEARNING MODEL IN THE SOCIAL STUDIES EDUCATION COURSE FOR ELEMENTARY SCHOOL TEACHERS IN THE ELEMENTARY SCHOOL TEACHER EDUCATION STUDY PROGRAM AT TADULAKO UNIVERSITY - Madokala, Avi Frianto; Iskandar; Misnah; Bau Ratu; Sunarto Amus; Hasdin Hanis; Ahdiah Diny; Rosyida (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2025)
Learning at the tertiary level has an important role in preparing competent and competitive prospective teachers. In the Elementary School Teacher Education (PGSD) Study Program at Tadulako University, the Social Science Education (IPS) course is one of the essential curriculum components. This study aims to develop hypercontent-based social studies teaching materials in the PGSD study program at Tadulako University. The research problems include: (1) the development of a hypercontent-based social studies learning model for basic education and (2) the feasibility of these teaching materials. This research uses the Research and Development (R&D) method using the Rowntree model, which consists of three stages: Planning, Writing Preparation, and Writing and Rewriting. Data were collected through literature studies, questionnaires, and learning outcome tests, and analyzed qualitatively and statistically. Validation results indicated the feasibility of the learning materials, with scores from linguists (4.5), media experts (4.3), content experts (4.4), and student readability (4.08), all categorized as “Excellent”. The effectiveness of this module was further confirmed by the test results, where more than 70% of the students answered the questions correctly. These findings indicate that hypercontent-based teaching materials are feasible and effective for use in social studies learning in the PGSD study program at Tadulako University.